Der „Bienenkorb“, eine neue morphologische Form aus Nord-Queensland, Nord-Australien - Twidale, Charles Rowland (ERDKUNDE, 1956)
Two examples of cone-shaped rocks of sandstone termed beehives are described from North Queensland, Australia. The features are attributed to the weathering of a well-jointed and well-bedded sandstone which disintegrates to give a fine grained - and hence easily removable - debris. They are likened to tors. A photograph of one example of the beehive form and a diagram illustrating its postulated evolution are given.